FEATURES OF GEOPHYSICAL RESEARCHES AT DETERMINATION OF FIRMNESS OF SLOPES AT THE GAS PIPELINES AREAS - KRYVIUK, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The complex approach to calculation of stability of a slope in view of geophysical data is developed and entered. Results of the complex approach to an estimation of sliding dangers on an example of two sliding sites in area of gas mains are analysed.